Integral Membrane Properties of Polysulfone/Chitosan/Polyvinyl Alcohol Blend Incorporated with Rice Husk Ash Silica Gel - Nur Syazwanie Izzati Chik; Norin Zamiah Kassim Shaari (Universitas Gadjah Mada, 2023)
In this study, silica gel was extracted from rice husk ash using a modified acid-leaching process. The gel was then characterized using an X-ray Diffractometer (XRD) and an X-ray Fluorescence (XRF). At different loadings of 0, 0.05 and 0.10 wt.%, silica gel was used as a cross-linker in the membrane formulation. Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) were used to characterize the membranes, while their performance was determined by pure water flux. XRD and XRF results revealed that the gel contained 76.85% silica. The presence of silica gel in membranes results in optimal water flux, indicating that the membranes have achieved good integral stability via the cross-linking process. Based on these positive findings, the applications of the membranes in the water-oil separation process will be evaluated in future work.